Financial valuation: Applications and models - Hitchner, James R. (New Jersey John Wiley & sons, Inc., 2025)
A comprehensive guide to the theory and application of valuation, along with useful models, tools, and tips for analysts Financial Valuation: Applications and Models provides authoritative reference and practical guidance on the appropriate, defensible way to prepare and present business valuations. With contributions by 30 top experts in the field, this updated edition provides an essential resource for those seeking the most up-to-date methods, with a strong emphasis on applications and models.